Value of Rapid Antigen Test in Comparison with Reverse Transcriptase-Polymerase Chain Reaction Method in the Diagnosis of COVID-19 - Alireza MIRAHMADIZADEH; Babak Shirazi YEGANEH; Jafar HASSANZADEH; Leila BADIEE; Mohebat VALI; Zahra MALEKI; Ali AKBARI; Tahereh PAKDEL; Haleh GHAEM (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Using the rapid antigen test (RAT) before exhausting the reverse transcriptase-polymerase chain reaction (RT-PCR) test’s capacity is crucial to enhance suitable detection of patients and timely reception of results. Therefore, this study was done to evaluate the sensitivity and specificity of RAT and compare it with the RT-PCR method in the diagnosis of Coronavirus disease-2019 (COVID-19). Materials and Methods: This study was performed on 634 individuals referred to public sampling centers performing the COVID-19 test in Shiraz City, Fars Province, Southern Iran. The sampling process was done following a multi-stage stratified protocol. The COVITECH® one-step real-time RT-PCR kit method as the reference standard test was compared with the RAT using E-Health Barakat Company® rapid antigen kit in the pharyngeal specimens. The trained personnel collected the data. Sensitivity, specificity, positive predictive value (PPV), negative predictive value, and the accuracy of the RAT were calculated using the MedCalc software. Moreover, the Kappa value was used to assess the level of agreement between RT-PCR and RAT. Results: According to the results of the RT-PCR method as a reference test; sensitivity, specificity, Kappa value, and accuracy of the RAT were 81.82%, 92.28%, 63.8%, and 91.01%, respectively in the diagnosis of COVID-19. In asymptomatic individuals, the specificity and the PPV of the RAT were 100%. Conclusion: In conclusion, our results suggested that a positive RAT provides considerable information for diagnosing COVID-19 in adults. As a result, in general, due to the high sensitivity, specificity, and accuracy of the RAT, it can be replaced with the RT-PCR test considering factors such as time, cost, and speed.